Dysregulated myosin in Hermansky-Pudlak syndrome lung fibroblasts is associated with increased cell motility - Jewel Imani; Steven P. M. Bodine; Anthony M. Lamattina; Diane D. Ma; Shikshya Shrestha; Dawn M. Maynard; Kevin Bishop; Arinze Nwokeji; May Christine V. Malicdan; Lauren C. Testa; Raman Sood; Benjamin Stump; et al. (Respiratory Research, 2022)
Abstract Hermansky-Pudlak syndrome (HPS) is an autosomal recessive disorder characterized by improper biogenesis of lysosome-related organelles (LROs). Lung fibrosis is the leading cause of death among adults with HPS-1 and HPS-4 genetic types, which are associated with defects in the biogenesis of lysosome-related organelles complex-3 (BLOC-3), a guanine exchange factor (GEF) for a small GTPase, Rab32. LROs are not ubiquitously present in all cell types, and specific cells utilize LROs to accomplish dedicated functions. Fibroblasts are not known to contain LROs, and the function of BLOC-3 in fibroblasts is unclear. Here, we report that lung fibroblasts isolated from patients with HPS-1 have increased migration capacity. Silencing HPS-1 in normal lung fibroblasts similarly leads to increased migration. We also show that the increased migration is driven by elevated levels of Myosin IIB. Silencing HPS1 or RAB32 in normal lung fibroblasts leads to increased MYOSIN IIB levels. MYOSIN IIB is downstream of p38-MAPK, which is a known target of angiotensin receptor signaling. Treatment with losartan, an angiotensin receptor inhibitor, decreases MYOSIN IIB levels and impedes HPS lung fibroblast migration in vitro. Furthermore, pharmacologic inhibition of angiotensin receptor with losartan seemed to decrease migration of HPS lung fibroblasts in vivo in a zebrafish xenotransplantation model. Taken together, we demonstrate that BLOC-3 plays an important role in MYOSIN IIB regulation within lung fibroblasts and contributes to fibroblast migration.